"Why are we saving All these artist publications + Other Galleries stuffs?" The Emergence of Artist-Run Culture in Halifax. DALHOUSIE ART GALLERY - Young, Rebecca (Archivaria, 2016)
“Why are we saving All these artist publications + Other Galleries stuffs?” The Emergence of Artist-Run Culture in Halifax. DALHOUSIE ART GALLERY, HALIFAX. 22 January–17 April 2016. Curated by CREIGHTON BARRETT and PETER DYKHUIS.